Hypolipidemic effect of aqueous extract of Gentianella thyrsoidea (Hook.) Fabris (Japallanshacoc) in Sprague Dawley rats - Huamán Saavedra, Juan (2019)
Gentianella thyrsoidea (Hook.) Fabris is an herbaceous species that grows in localities of the north of Peru, at 3800-4900 m.a.s.l. Despite the wide popular use, no studies have been found to determine its lipid-lowering activity, so this research is aimed to evaluate the hypolipidemic effect of aqueous extract of Gentianella thyrsoidea in Sprague Dawley rats with induced hyperlipidemic. Twenty-four male specimens of Rattus norvegicus Sprague Dawley strain were randomly divided into two experimental groups (EG1 and EG2) and one control group (CG). Every group was induced to hyperlipidemia by administration of 2.5 ml/day of fused tallow trough orogastric way per two weeks. They were given treatment for three weeks: aqueous extract of Gentianella thyrsoidea to experimental groups (250 mg/kg and 500 mg/kg respectively) and saline solution to control group. Basal, post-induction and post-treatment plasma lipid profile was measured. Cholesterol, triglycerides and LDL levels showed significant differences between groups (p <0.05) after treatment. Cholesterol decreased 20.7% and 19.4% in EG1 and EG2 respectively, in CG increased 0.91%; triglycerides decreased 49.63% and 41.55% in EG1 and EG2 respectively, in CG decreased 18.76% but it was not significant; LDL decreased 34.64% and 28.24% in EG1 and EG2 respectively, in CG increased by 7.58%. The aqueous extract of Gentianella thyrosidea significantly decreased the levels of total cholesterol, triglycerides and LDL, evidencing to be a therapeutic alternative for the treatment of dyslipidemias.